2017
DOI: 10.3382/ps/pew266
|View full text |Cite
|
Sign up to set email alerts
|

Application of pigeon circovirus recombinant capsid protein for detecting anti-PiCV antibodies in the sera of asymptomatic domestic pigeons and the potential use of a combination of serological and molecular tests for controlling circovirus infections in pigeon breeding flocks

Abstract: The aim of this study was to evaluate the serologic status of domestic pigeons not infected and asymptomatically infected with the pigeon circovirus (PiCV) with the use of an enzyme-linked assay based on PiCV recombinant capsid protein as a plate antigen. Recombinant PiCV capsid protein was produced by transforming E. coli BL21 (DE3) Rosetta colonies with expression plasmids.Blood samples and cloacal swabs were collected from 171 asymptomatic pigeons. The birds were divided into two groups (infected and not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 24 publications
1
32
0
Order By: Relevance
“…Daum et al (2009) conducted a retrospective study of pigeon sera obtained in 1989, 1991 and 2008 and found anti-PiCV antibodies in 78% (61%-90%) of the tested samples on average. A recent serological study of Polish domestic pigeons from selected breeding flocks revealed the presence of anti-PiCV antibodies in 72% birds on average, regardless of their infection status (average prevalence of 36%) (Stenzel et al 2016). Somewhat different results were reported by who found anti-PiCV antibodies in 96% of the examined pigeons, but their study was performed on a very small population of 28 birds.…”
Section: Epidemiology Of Picv Infectionsmentioning
confidence: 88%
See 3 more Smart Citations
“…Daum et al (2009) conducted a retrospective study of pigeon sera obtained in 1989, 1991 and 2008 and found anti-PiCV antibodies in 78% (61%-90%) of the tested samples on average. A recent serological study of Polish domestic pigeons from selected breeding flocks revealed the presence of anti-PiCV antibodies in 72% birds on average, regardless of their infection status (average prevalence of 36%) (Stenzel et al 2016). Somewhat different results were reported by who found anti-PiCV antibodies in 96% of the examined pigeons, but their study was performed on a very small population of 28 birds.…”
Section: Epidemiology Of Picv Infectionsmentioning
confidence: 88%
“…The prevalence of PiCV was determined by age and health status, and it was the highest (close to 100%) in young birds showing non-specific symptoms of the disease (Stenzel et al 2012). Asymptomatic infections were noted in 53% birds of all ages on average, and in 36% of adult domestic pigeons from breeding flocks (Stenzel & Pestka 2014;Stenzel et al 2014a;Stenzel et al 2016). Similar results were reported in studies of domestic pigeons conducted in Hungary (prevalence of less than 57%) and in China where PiCV DNA was isolated from 80.7% of diseased birds and 63.4% of asymptomatic birds (Zhang et al 2011;Cs agola et al 2012).…”
Section: Epidemiology Of Picv Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of PiCV is determined by age and health status, and affects about 70% of the global pigeon population on average [ 5 , 6 , 7 ]. Asymptomatic infections with this virus are quite common and account for 36–53% of the population [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%